Evaluasi Kurikulum Merdeka di SDN 156 Palembang: Harapan, Tantangan, dan Realitas - Sofiana, Ayun; Lubis, Elfira Rossa; Agustina, Keyla; Abdurrahmansyah (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study discusses the evaluation of the implementation of the Independent Curriculum (Kurikulum Merdeka) at SDN 156 Palembang, one of the public elementary schools that adopted the new curriculum. The purpose of this research is to analyze the effectiveness of the curriculum implementation and to understand teachers’ and students’ perceptions toward it. This research uses a descriptive qualitative approach, with data collected through direct interviews with one teacher and two fourth-grade students. The findings indicate that the Independent Curriculum has brought positive changes to the learning process, especially in creating a more interactive and student-centered classroom environment. Teachers have started applying various methods such as Project-Based Learning (PBL), group discussions, and audiovisual media to encourage student participation and learning motivation. However, limited facilities, insufficient digital tools, and the need for teacher readiness remain major challenges. Overall, the Independent Curriculum has great potential to improve learning quality if supported by continuous teacher training and adequate educational infrastructure.